PF.53 Do Computerised Cardiotograph Results Change Management During Pregnancy For Women with Diabetes Who Have a Macrosomic Fetus Diagnosed by Ultrasound Examination?. (26th April 2013) - Auchterlonie, H; Farrar, D; Tuffnell, D
Abstract : Background: Pregnancy complicated by diabetes causes concern for the health of the fetus particularly when ultrasound examination indicates macrosomia. This has led clinicians (in the absence of beneficial evidence) to instigate fetal surveillance. All women with diabetes at the Bradford Women's and Newborn unit are offered twice weekly computerised cardiotographs (CTG) if on ultrasound scan their fetus has an abdominal circumference >95 th centile. Our aim was to investigate if this policy affected the management and outcomes for women with diabetes. Method: A retrospective three year analysis of all women with diabetes, with an USS indicating fetal macrosomia, who attended hospital for routine CTG between 2009 and 2011. Results: One hundred pregnancies were identified. 83 women had pre-existing and 17 had gestational diabetes (GDM). 26 cases had a total of 48 failed CTGs of which 38 failed only because of an absence of high variation. Of the women with pre-existing diabetes, 11 (13%) had one or more failed CTGs, of the women with GDM 15 (88%) had one or more failed CTGs. Only three women received an intervention following a failed CTG. Risk of admission to special care was unaffected by CTG results. One woman with 4 failed CTGs out of 11 suffered a stillbirth and one woman who had no failed CTGs suffered a stillbirth. Conclusion: Surveillance of fetal wellbeing in women with diabetes with a macrosomic infant using computerised CTGs does not seem to affect management of pregnancy or perinatal outcomes. Repeated CTGs do not seem to be of benefit in maternal diabetes.